2017
DOI: 10.1200/jco.2017.35.18_suppl.lba1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective pooled analysis of six phase III trials investigating duration of adjuvant (adjuv) oxaliplatin-based therapy (3 vs 6 months) for patients (pts) with stage III colon cancer (CC): The IDEA (International Duration Evaluation of Adjuvant chemotherapy) collaboration.

Abstract: LBA1 Background: Since 2004, 6 months (m) of oxaliplatin (oxali)-based treatment has been the standard of care as adjuvant therapy for stage III CC. Since oxali is associated with cumulative neurotoxicity, shorter duration of adjuv therapy could spare pts toxicity and lead to substantial saving in health expenditures. Methods: A prospective, pre-planned pooled analysis of 6 concurrently conducted randomized phase III trials (SCOT, TOSCA, Alliance/SWOG 80702, IDEA France (GERCOR/PRODIGE), ACHIEVE, HORG) was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 0 publications
1
39
0
2
Order By: Relevance
“…There was no significant difference in OS between those receiving 3-5 versus 6-9 cycles of platinum-based first-line chemotherapy (HR 1.02, p=0.91). We also observed no significant interactions with the type of platinum and "completed planned chemotherapy" as defined by the and recent data also suggest that 3 months of adjuvant therapy may be adequate [27][28][29] . In the case of ovarian cancer, 6 cycles of platinum-based chemotherapy are targeted by convention, with no data refining the necessity of 6 cycles 30 .…”
Section: Discussionsupporting
confidence: 56%
“…There was no significant difference in OS between those receiving 3-5 versus 6-9 cycles of platinum-based first-line chemotherapy (HR 1.02, p=0.91). We also observed no significant interactions with the type of platinum and "completed planned chemotherapy" as defined by the and recent data also suggest that 3 months of adjuvant therapy may be adequate [27][28][29] . In the case of ovarian cancer, 6 cycles of platinum-based chemotherapy are targeted by convention, with no data refining the necessity of 6 cycles 30 .…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, the risk of early recurrence in patients with RDI-O < 60% concerned especially low-risk group. These results should be referred to the abovementioned IDEA project and CAPOX e cacy in low-risk group [20][21][22]. It seems, that RDI-O may be a more accurate re ection of the true patient-relevant bene t of adjuvant chemotherapy among stage III CC.…”
Section: Discussionmentioning
confidence: 87%
“…Tsai et al have shown that at least eight FOLFOX cycles are needed to have OS bene t, and seven to ensure DFS [19]. Moreover, in the International Duration Evaluation of Adjuvant Therapy (IDEA) project in stage III CC patients, the noninferiority of FOLFOX/CAPOX regimens used for 3 vs. 6 months was not demonstrated [20][21][22]. Although in the lower risk group (pT1-3/N1), the 3-month (4 cycles) CAPOX was as effective as the 6-month (8 cycles) treatment and the 3-year rate of DFS was 74.6% and 75.5%, respectively [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…15 % der Patienten noch nach 4 Jahren an einer klinisch relevanten peripheren Neuropathie. Auf dem ASCO 2017 wurde die IDEA-Initiative als Abstrakt Nummer 1 in der Plenarsitzung vorgestellt, die in einer internationalen Kollaboration die Nicht-Unterlegenheit einer dreimonatigen adjuvanten Oxaliplatin-Kombination gegenüber einer sechsmonatigen Therapie prüfte [22]. Auf dem ESMO wurden diese Daten aktualisiert [23].…”
Section: Adjuvante Therapie Des Kolonkarzinomsunclassified